A dash of christmas ebook Montgomery brothers series, book 10. - Chase, Samantha (Montgomery Brothers, 2019)
"The perfect blend of heart and sass."—Publishers Weekly for Holiday Spice With a dash of Christmas magic... Two people who have spent most of their lives being rivals... Learn a little something about following their hearts... Carter Montgomery broke the family mold when he went to culinary school. Now a successful restauranteur, he's at a crossroads: should he continue on his successful path or look for a new challenge? What he needs is time alone to think things through. But his matchmaking family has other ideas... Emery Monaghan's no-good fiancé has embroiled her in scandal and she needs a way out. When mentor Eliza Montgomery offers her a refuge, she's relieved—until she realizes that the deal means rubbing elbows with Eliza's son Carter—Emery's childhood nemesis. The Montgomery Brothers series: Wait for Me (Book 1) Trust in Me (Book 2) Stay With Me (Book 3) More of Me (Book 4) Return to You (Book 5) Meant for You (Book 6) I'll Be There (Book 7) Until There Was Us (Book 8) Suddenly Mine (Book 9) Dash of Christmas (Book 10) Praise for Samantha Chase: "Utter rock star perfection. I dare you to stop reading until the end."—Rachel Van Dyken, New York Times Bestselling Author, for One More Moment "Chase's three-dimensional characters leap off the page, encouraging readers to sit down, put their feet up, and enjoy...charming."—Publishers Weekly for Until There Was Us "Chase just gets better and better."—Booklist